Research of the structure and properties of cermets based on nickel and aluminum oxide. (December 2020) - Agureev, L E; Kostikov, V I; Savushkina, S V; Eremeeva, Zh V; Laptev, I N; Ivanov, A V; Ashmarin, A A; Kanushkin, A I; Ivanov, B S
Abstract: In this work, the production of cermets in the system of nickel-aluminum alloy – aluminum oxide by the method of mechanical activation and spark plasma sintering was carried out. The analysis of the features of the microstructure of composites, phase analysis at room and elevated temperatures, as well as the dependence of the flexural strength on the temperature and composition of cermets are presented.